Epidemiological profile of gestational syphilis and congenital syphilis in a reference center in Northeast Brazil: risk factors and trend from 2019 to 2021 - Rodrigues Barbosa de Moraes, Alice; Gusmão de Almeida, Ana Beatriz; Labanca da Silva Azevêdo, Brenda; Manoel de Freitas, Gutemberg; Bezerra Menezes, Maria Luiza; Medeiros de Melo Barros, Rayssa; da Silva Coutinho, Victoria Lays (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Syphilis is an infectious systemic disease caused by the bacterium Treponema pallidum. The Amaury de Medeiros Integrated University Health Center in Recife is a reference maternity hospital for high-risk pregnancies and the management of the most common Sexually Transmitted Infections during prenatal care, including Gestational Syphilis and Congenital Syphilis. Objective: To determine the epidemiological profile of the population exposed to these conditions, the rate of Gestational Syphilis detection, the incidence of Congenital Syphilis, and the associated unfavorable outcomes in Amaury de Medeiros Integrated University Health Center between January 2019 and December 2021. Methods: This retrospective cohort study included pregnant women and neonates diagnosed with syphilis at Amaury de Medeiros Integrated University Health Center. Data were collected from the Notification/Investigation Forms for Gestational Syphilis and Congenital Syphilis, between January 2019 and December 2021. Results: At Amaury de Medeiros Integrated University Health Center, 463 cases of Gestational Syphilis and 296 of Congenital Syphilis were reported. During the three-year study, 4444, 4360, and 4265 live births were recorded, confirming the Gestational Syphilis detection rates — 33.30, 36.92, and 36.10 per 1000 live births, with the incidence of Congenital Syphilis being 26.1, 21.33, and 20.39 per 1000 live births. Pregnant women in their third trimester who were brown, had incomplete primary education, and lived in an urban area were the main sociodemographic variables. In total, 217 (73.3%) patients were diagnosed with Gestational Syphilis during or after delivery, indicating a low prenatal coverage (70.6%). In terms of the progression of Congenital Syphilis, unfavorable outcomes was found in 40 (13.5%) patients, including 16 (40%) abortions, 10 (25%) stillbirths, nine (22.5%) deaths from Congenital Syphilis, and 5 (12.5%) deaths from other causes. Conclusion: Gestational Syphilis detection rates and Congenital Syphilis incidence remain alarming, with abortions and stillbirths being the most common unfavorable outcomes. To change the dramatic situation of Congenital Syphilis in Brazil, the associated factors point to a poor quality of prenatal care and an urgent need to change public policies for pregnant women and newborns, in conjunction with socioeconomic assistance.